Imagining “Bangsa Malaysia”: race, religion and gender in Lloyd Fernando’s green is the colour - Quayum, M.A. (Taylor & Francis, 1999)
The flurry of theoretical activity on the concept of "nation," or what Benedict Anderson defines as "imagined community," shows how deeply ingrained the idea is in contemporary imagination. Although, like race and gender, nation is a "fictive" concept, having little or no scientific grounding, it has been, as Anderson aptly suggests, "the most universally legitimate value in the political life of our time" (12). Dipesh Chakrabarty is of the view that European imperialism and Third World nationalism have together achieved the "universalisation of the nation-state as the most desirable form of political community" (19).